Cholera in Zambia: Evaluating Emergency Response and the Limits of Reactive Public Health Systems - Juliet Mwale; Lissa Ceolin (Global Health Cases, 2026)
Abstract Cholera remains a recurrent public health challenge in Zambia, with repeated outbreaks disproportionately affecting low-income urban and peri-urban populations, particularly in Lusaka Province. Seasonal rainfall and flooding intensified by climate change repeatedly overwhelm sanitation systems and contaminate water sources. This is particularly true where pit latrines and shallow wells coexist in Lusaka and other flood-prone areas. This case study summarizes the epidemiology and factors associated with cholera transmission using the 2017–2018 and 2023–2024 outbreaks as focal points. It links the disease to structural determinants including inadequate water, sanitation, and hygiene (WASH) services, weak drainage infrastructure, health system constraints, and governance challenges. The seasonal flooding during the rainy season increases exposure by inundating sanitation facilities and contaminating shallow groundwater and alternative water sources in informal settlements, creating conditions that support repeated transmission cycles. The recurrent clustering of cases in the same peri-urban neighbourhoods of Lusaka over time proves that exposure pathways remain largely unchanged between outbreaks. This shows cholera as a predictable outcome of environmental and social conditions. This case recounts response measures across primary, secondary, and tertiary prevention, which include WASH services, oral cholera vaccination, surveillance and laboratory confirmation, risk communication, and clinical management through rehydration therapy and antibiotics. It also identifies barriers to prevention, including reactive financing, infrastructure deficits, limited laboratory capacity, vaccine supply constraints, and community mistrust shaped by prior emergency responses. The case situates cholera risk as the intersection of climate hazards, urban development, environmental infrastructure, and social inequities, illustrating the importance of governance, equity, and community trust in shaping cholera prevention and response. Information © The Authors 2026